THE CONCEPT OF GAMIFICATION IN THE TRAFFIC CRIMINAL SYSTEM IN INDONESIA - Aloysius Bernanda Gunawan (Bhayangkara Law Review, 2024)
The use of game elements in non-game situations with the aim of increasing positive learning behavior is known as gamification. This paper aims to investigate the concept of gamification in the Indonesian light traffic criminal system. Incorporating gamification components such as points, levels, badges, rankings, and avatars to improve compliance with traffic regulations is a key goal. To understand the potential of gamification in traffic law, this research looked at related literature and regulations. The findings show that gamification can be used to increase awareness and compliance of traffic laws effectively. Gamification elements such as points and badges provide positive incentives, while levels and rankings offer motivating feedback. Avatars help in personalizing the user experience. Gamification in the light traffic criminal system can be a creative way to improve legal compliance by providing road users with a more interactive and engaging approach.